Early detection of fissure caries in permanent first molars: A comparative in vivo study of traditional and digital diagnostic approaches - Hala El Akhras; Marlène Khoury Freiha; Hani Tohme; Nada Farhat Mchayleh; Nathalie Kabbani; Joy Elian El Hayek (Contemporary Pediatric Dentistry, 2025)
Aim: This study aimed to compare the performance of various diagnostic methods in detecting early fissure caries in permanent first molars. The evaluated methods included visual examination, tactile examination with a probe, a laser fluorescence (LF) device (DIAGNOdent® Pen), and an intraoral scanner (TRIOS 5®) with and without the caries detection aid. By integrating emerging digital tools alongside conventional techniques, this study explored their potential to enhance diagnostic precision, particularly in pediatric patients. Methods: This study was conducted at the Faculty of Dental Medicine, Saint Joseph University, Beirut, and assessed pit and fissure caries in 15 children aged 6 to 10 years, involving 37 permanent first molars. Each child’s permanent first molars were initially evaluated to ensure they met the study’s inclusion criteria. The study included a 30-minute session in which each molar underwent visual and tactile examinations, DIAGNOdent® Pen assessment, and TRIOS 5® evaluation, both with and without the caries detection aid. Data from all examinations were collected and subjected to statistical analysis. Results: Caries detection rates were highest for both the DIAGNOdent® Pen and TRIOS 5® with the caries detection aid, each identifying caries in 83.8% of cases. The tactile examination exhibited a slightly higher detection rate (62.2%) compared to both visual inspection and TRIOS 5® without the caries aid, which showed similar and lower detection rates (59.5%). Conclusions: The findings of this study demonstrated that the DIAGNOdent® Pen and TRIOS 5® with the caries detection aid exhibited the highest caries detection rates, outperforming tactile and visual examinations. Embracing technological advancements in dental diagnostics is crucial for improving patient outcomes, highlighting the need for continued research and validation in modern dental care.